2022
DOI: 10.4103/ijo.ijo_1309_22
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different thickness scleral lens on corneal parameters in eyes with keratoconus

Abstract: Purpose: To investigate the impact of different-thickness scleral lenses (SLs) on corneal thickness, curvature, and fluid reservoir thickness in keratoconic eyes. Methods: Schiempflug imaging and AS-OCT was captured before and immediately following 6 h of SL wear. Different-thickness lenses were used while keeping the other parameters the same. The timing of the measurement for day 1 and day 2 was matched to allow for the control of the confounding influence of diurnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…There was no evidence of significant corneal edema in our patients up to a 3-month follow-up similar to previous studies in patients with keratoconus fitted with a scleral lens. Iqbal et al 23 showed that a scleral lens with a central lens thickness of 200 to 400 μm did not induce corneal edema after 6 hr of contact lens wear in patients with keratoconus. Cagliari et al 24 followed up with 22 patients with keratoconus who were fitted with scleral lenses for 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…There was no evidence of significant corneal edema in our patients up to a 3-month follow-up similar to previous studies in patients with keratoconus fitted with a scleral lens. Iqbal et al 23 showed that a scleral lens with a central lens thickness of 200 to 400 μm did not induce corneal edema after 6 hr of contact lens wear in patients with keratoconus. Cagliari et al 24 followed up with 22 patients with keratoconus who were fitted with scleral lenses for 90 days.…”
Section: Discussionmentioning
confidence: 99%
“…Scleral lens‐induced corneal oedema is of clinical concern due to the potential hypoxic sequelae that may arise following long‐term lens wear in both healthy and diseased eyes, such as peripheral neovascularisation and graft failure or rejection (following keratoplasty). The magnitude of central corneal oedema varies with scleral lens fitting parameters such as the fluid reservoir thickness, 1 lens thickness, 2–5 lens oxygen permeability 6,7 and the lens wear conditions (e.g., duration, 8 eyelid closure 9–11 ). While it is understood that mechanical interaction between the back surface of a scleral lens and the peripheral cornea should be avoided, 12,13 few studies have investigated corneal oedema following scleral lens wear beyond the mid‐periphery.…”
Section: Introductionmentioning
confidence: 99%
“…The fluid reservoir between the posterior lens surface and anterior cornea can neutralize irregular astigmatism of the anterior surface. [ 10 ] Conventional scleral lenses mask higher-order aberrations between 60% and 65%[ 11 12 ] through (1) approximate refractive index matching of the postlens tear layer and the cornea and (2) by providing a new, well-formed optical first refracting surface for light entering the eye. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%